Fibroblast Insights into the Pathogenesis of Ankylosing Spondylitis - Liu Z; Cai M; Ke H; Deng H; Ye W; Wang T; Chen Q; Cen S (Dove Medical Press, 2023)
Zhenhua Liu,1,* Mingxi Cai,2,* Haoteng Ke,2,* Huazong Deng,2 Weijia Ye,2 Tao Wang,1 Qifan Chen,1 Shuizhong Cen1 1Department of Spinal Surgery, Orthopedic Medical Center, Zhujiang Hospital, Southern Medical University, Guangzhou, 510280, People's Republic of China; 2The Second Clinical School, Zhujiang Hospital, Southern Medical University, Guangzhou, 510280, People's Republic of China*These authors contributed equally to this workCorrespondence: Shuizhong Cen, Department of Spinal Surgery, Orthopedic Medical Center, Zhujiang Hospital, Southern Medical University, Guangzhou, People's Republic of China, Tel +86 13480297160, Email censhzh3@mail2.sysu.edu.cnPurpose of the Review: Emerging evidence has shown that ankylosing spondylitis fibroblasts (ASFs) act as crucial participants in inflammation and abnormal ossification in ankylosing spondylitis (AS). This review examines the investigations into ASFs and their pathological behavior, which contributes to inflammatory microenvironments and abnormal bone formation. The review spans the period from 2000 to 2023, with a primary focus on the most recent decade. Additionally, the review provides an in-depth discussion on studies on ASF ossification at the cellular level.Recent Findings: ASFs organize immune functions by recruiting immune cells and influencing their differentiation and activation, thus mediate the inflammatory response in the early phase of disease. ASFs promote joint destruction at sites of cartilage and actively promote abnormal ossification by recruiting osteoblasts, differentiation into myofibroblasts or ossification directly. Many signaling pathways and cytokines such as Wnt signaling and BMP/TGF-β signaling are involved in ASF ossification.Summary: ASFs play a key role in AS inflammation and osteogenesis. Further studies are required to elucidate molecular mechanisms behind that and provide new targets and directions for AS diagnosis and treatment from a new perspective of fibroblasts.Keywords: ankylosing spondylitis, fibroblast, inflammation, ossification